Construction of a High-Density Genetic Map and Identification of Loci Related to Hollow Stem Trait in Broccoli (Brassic oleracea L. italica) - Yu, Huifang; Wang, Jiansheng; Zhao, Zhenqing; Sheng, Xiaoguang; Shen, Yusen; Branca, Ferdinando; Gu, Honghui (Frontiers in Plant Science, 2019)
A high-quality genetic map is important for mapping of compound traits. In this study, a genetic map was constructed based on the reference genome TO1000 after specific locus amplified fragment (SLAF) sequencing in a double-haploid segregation population of broccoli, and loci controlling hollow stem trait were identified in the genetic map. The genetic map contains 4,787 SLAF markers, with a mean marker distance of 0.22 cM and the mean sequencing depths of 91.14-fold in the maternal line, 88.97-fold in the paternal line and 17.11-fold in each DH progeny. A locus controlling the hollow stem trait, QHS.C09-2, which could explain 14.1% of the phenotypic variation, was steadily detected on the linkage group 9 in the indicated data of three years’ trials and BULE analysis. The genetic map could lay an important foundation for mapping of compound traits, and mapping of hollow stem trait would be basis to clone the genes related to hollow stems in broccoli.